Topical Theme Analysis in Recount Texts from an English for Nusantara Textbook: An SFL-Based Study - Rahmadiani, Ghania Balqis; Ambarwati, Evi Karlina; Setiawan, Wawan; Salsabila (Lembaga Pengembangan Kinerja Dosen, 2026)
The analysis of themes in a recount text shows how the text is organized. One of the essential themes to analyze is the topical theme, as it represents the clause and reflects the writer's ability to convey the content of the text. This study aims to identify the forms and types of topical themes that are dominantly used in recount texts in English textbooks for junior high school grade 9 based on the concept of Systemic Functional Linguistics. The research data were four recount texts taken from chapter two. The data is organized into clauses through a qualitative approach with a content analysis research design. All clauses were analyzed based on the types of themes and rheme. The analysis results show that there are 97 topical themes. Most topical themes were participants (78.4%) and circumstances (21.6%). In addition, the recount texts did not have process as the central theme. The dominant type of topical theme found is the unmarked theme, followed by the marked theme. This study's findings reinforce the importance of explicitly teaching the elements and types of topical themes found in the self-contained curriculum teaching materials to support language learning in junior high schools.